Can Early Life-Stages of the Marine Fish Sparus aurata be Useful for the Evaluation of the Toxicity of Linear Alkylbenzene Sulphonates Homologues (LAS C10-C14) and Commercial LAS?. (2002) - Hampel, M.; Moreno-Garrido, I.; Blasco, J.
Abstract : Most commercial household cleaning agents and personal care products contain the anionic surfactant linear alkylbenzene sulphonates (LAS) as the active compound. After their use they are discharged, theoretically after adequate wastewater treatment, into receiving waters finally reaching estuaries and coastal waters. Laboratory toxicity tests are useful tools in determining at which concentration a certain wastewater compound becomes hazardous for an existing group of organisms. Early life-stage toxicity tests include exposure during the most sensitive development period of the organism. In fish, this type of assay has shown to predict accurately maximum acceptable toxicant concentration (MATC) values (comprised in the range defined by the NOEC and LOEC) in fish early life-stage tests. For this reason, larvae of the seabream, Sparus aurata, were exposed to increasing concentrations of LAS homologues (C10 -C14 ) and commercial LAS. Obtained LC50 values ranged between 0.1 and 3.0 mg l -1 and were compared with LC50 values of previous hatching experiments with the same species. Larvae proved to be more sensitive to LAS exposure of individual homologues than eggs, except in the case of commercial LAS. LC50 values can be directly employed to determine their potential risk in a concrete environment with known pollutant concentrations. Dividing the LC50 value with the found homologue concentration and extrapolating with certain security factors proposed by different environmental organisms, potentially hazardous pollutant concentrations may be detected. Average estuarine or coastal LAS concentrations are generally below toxicity limits for this kind of organism, considering that the average alkyl chain length of commercial LAS is 11.6 carbon atoms.